Fabrications of the Greek Past - Touna, Vaia (Supplements to Method and Theory in the Study of Religion Ser, 2017)
Contents -- Preface -- Acknowledgements -- Introduction: A Complicated Affair -- Chapter 1. Gloria Patri: The Construction of the Modern Self -- Chapter 2. Matters of Classification: The Case of ``Mysteries'' -- Chapter 3. Representations of the Ruined Past: Making Self and Other -- Chapter 4. Traditioning Acts of Identification: The Case of Greek ``Traditional'' Villages -- Epilogue: The Ever-Present Past -- References -- Index.